PENGEMBANGAN KARIER DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN PADA CV. DAFA BETUAH BELITANG OKU TIMUR - Yansahrita, Yansahrita; Mardani, Mardani; Kurniawan, Deni (AKTUAL, 2025)
Career development is one of the important things in carrying out a task and responsibility, in order to maximize the results achieved. This factor is very necessary for every agency or company that is carrying out a mission and effort in achieving success, because career development will be useful for the employee themselves and the agency or company concerned. This study aims to determine the effect of career development on employee performance at CV. Dafa Betuah Belitang, East OKU Regency. This study uses a quantitative approach with data collection techniques through questionnaires. Data collection methods use observation, interviews, questionnaires and documentation. From the results of the calculation, it turns out that t count = 0.877 is obtained, then when connected with t table, the confidence number is 0.95, which means the error rate is 0.05, which shows the number 1.860, thus meaning t count is smaller than t table (0.877 <1.860). With these results, it means that Ha is rejected and Ho is accepted, meaning that there is a low influence between career development on employee performance at CV. Dafa Betuah Belitang, East OKU Regency. Correlation between the influence of career development on employee performance at CV. Dafa Betuah Belitang OKU Timur obtained the number r = 0.288, after consulting with conservative standards, it turns out to be located at a low correlation, which means there is a low correlation between career development and employee performance at CV. Dafa Betuah Belitang OKU Timur.